PELATIHAN PENULISAN PROPOSAL KEGIATAN SISWA MADRASAH DI MAN 1 KOTA TANGERANG SELATAN - Nanang; Lely Panca Andriyanto; Sartika Lina Mulani Sitio (AMMA : Jurnal Pengabdian Masyarakat, 2023)
MAN 1 Kota Tangerang Selatan is located in Desa Kademanagan, Kec. Setu, Tangerang Selatan. Students at this are graduates from Tsanawiah and from Islamic boarding schools. The purpose of this service is to increase students' understanding of activity proposals held within the madrasah environment or activities outside the madrasah and to improve students' skills in writing activity proposals properly and correctly. What is needed by students is training in writing activity proposals because so far it has been considered not good enough. The methods used in this community service activity are observation, training and mentoring (practice of making student activity proposals). Through interviews with the Deputy Head of Student Affairs and the heads of the extracurricular MAN 1 Kota Tangerang Selatan, data was obtained that these students had difficulties in compiling activity proposals. Furthermore, through observation activities it was found that after the training activities students experienced an increase in the skills of preparing activity proposals. The result of the implementation of the activity is that students who take part in the training (heads of extracurricular activities) have a good understanding of making activity proposals and know and have the ability to compile activity proposals organized by so that they can apply them to activities other.